2021
DOI: 10.1002/anie.202105032
|View full text |Cite
|
Sign up to set email alerts
|

Hypsochromic Shift of Multiple‐Resonance‐Induced Thermally Activated Delayed Fluorescence by Oxygen Atom Incorporation

Abstract: Herein, we reported an ultrapure blue multipleresonance-induced thermally activated delayed fluorescence (MR-TADF) material (n-DABNA-O-Me) with a high photoluminescence quantum yield and a large rate constant for reverse intersystem crossing. Because of restricted p-conjugation of the HOMO rather than the LUMO induced by oxygen atom incorporation, n-DABNA-O-Me shows a hypsochromic shift compared to the parent MR-TADF material (n-DABNA). An organic light-emitting diode based on this material exhibits an emissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
128
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 190 publications
(136 citation statements)
references
References 72 publications
(9 reference statements)
7
128
0
1
Order By: Relevance
“…In the past few years, TADF with MR effect induced HOMO–LUMO separation has shown great potential to deliver a narrow EL band. 91–94 For example, Hatakeyama et al first reported two MR-TADF compounds with a B–N-containing core skeleton, which exhibited blue EL with a small FWHM of only 28 nm, a high maximum EQE max of 20.2%, and high color purity with CIE coordinates of (0.13, 0.09) which are close to the National Television System Committee (NTSC) blue light standard (CIE: (0.14, 0.08)). 95 The as-synthesized compounds with tert -butyl and carbazolyl units were subsequently modified and achieved blue OLEDs with a FWHM of only 27 nm, a high EQE max of 32.1%, and low efficiency roll-off.…”
Section: Application Of Pure Organic Rtp and Tadf Emitters In Electro...mentioning
confidence: 95%
“…In the past few years, TADF with MR effect induced HOMO–LUMO separation has shown great potential to deliver a narrow EL band. 91–94 For example, Hatakeyama et al first reported two MR-TADF compounds with a B–N-containing core skeleton, which exhibited blue EL with a small FWHM of only 28 nm, a high maximum EQE max of 20.2%, and high color purity with CIE coordinates of (0.13, 0.09) which are close to the National Television System Committee (NTSC) blue light standard (CIE: (0.14, 0.08)). 95 The as-synthesized compounds with tert -butyl and carbazolyl units were subsequently modified and achieved blue OLEDs with a FWHM of only 27 nm, a high EQE max of 32.1%, and low efficiency roll-off.…”
Section: Application Of Pure Organic Rtp and Tadf Emitters In Electro...mentioning
confidence: 95%
“…Since then, research efforts on modification or decorating ν‐DABNA to get blueshifted emission have been continuously explored. [ 6,22–25 ] However, to the best of our knowledge, blue OLED with EQE >20% and satisfies the Rec.2020 standard (i.e., CIE y < 0.05) have not yet been reported. Moreover, it is reported that device performance of ν‐DABNA is highly sensitive to doping ratio (EQE max ranging from 13.3% to 34.4% and CIE y coordinates ranging from 0.11 to 0.23 were reported) and excimer quenching can occur even at a very low doping ratio (e.g., 1 wt%), which is ascribed to its planar π‐extended framework.…”
Section: Introductionmentioning
confidence: 97%
“…The resulting non-bonding molecular orbitals (MOs) minimise the vibronic coupling, leading to narrow luminescence. The multi-resonance effect also reduces the exchange interaction making these materials suitable for application in thermally activated delayed fluorescence (TADF) and the success of this approach has led to a significant number of experimental 11,[13][14][15][16][17][18][19][20][21] and theoretical [22][23][24] investigations into these systems, which have achieved high-performing 3rd-generation 11 and Hyperfluorescence OLEDs. 25 Despite the importance of the emission FWHM, there are few computational studies computing and/or predicting the emission FWHM of luminescent organic materials.…”
Section: Introductionmentioning
confidence: 99%